Three new species of Protearomyia McAlpine, 1962 (Diptera: Lonchaeidae) with a key to males of the Palearctic species - Macgowan, Iain (Zootaxa, 2014)
Three new species of Palearctic Protearomyia McAlpine, 1962 are described, P. iberica sp. nov., P. rameli sp. nov. and P. withersi sp. nov. These are compared with the three previously described species, a key is provided to the males of all the Palearctic species.